Targeting Radiotherapy to Cancer by Gene Transfer. Issue 2 (21st April 2003) - Mairs, R. J.; Boyd, M.
Abstract : Targeted radionuclide therapy is an alternative method of radiation treatment which uses a tumor-seeking agent carrying a radioactive atom to deposits of tumor, wherever in the body they may be located. Recent experimental data signifies promise for the amalgamation of gene transfer with radionuclide targeting. This review encompasses aspects of the integration of gene manipulation and targeted radiotherapy, highlighting the possibilities of gene transfer to assist the targeting of cancer with low molecular weight radiopharmaceuticals.